PENTINGNYA BAHASA INGGRIS UNTUK ANAK–ANAK DAN REMAJA NAGARI LIMAU PURUT TAPAN - Herayati, Herayati; Irawan, Yoki; Ramdani, Ramdani (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2022)
In today's modern world and the high level of competition, everyone is expected not only to have a high level of education but also to require special skills or what we usually call "skills." One of the "skills" currently needed is English language skills. The role of English is necessary both in mastering communication technology and interacting directly. As a means of global communication, English must be mastered actively, both spoken and written. This teaching activity focuses on increasing interest in learning English among children and teenagers in Nagari Lalang Panjang. The goal is to increase interest in learning and improve English language skills (soft skills). Some of the methods PKM students use are question and answer and discussion methods to identify knowledge and supporting technology. The lecture method is used during learning and theoretical understanding of English. The results achieved are: 1. They understand the importance of learning English as children. 2. Children will become familiar with English. 3. many children and teenagers are not interested in the importance of learning English.